Uzbekistan’s initiatives in the framework of the united nations and its role in global politics: a 2016–2025 analysis - Bahrom Yuldoshovich Yusufjonov (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The article analyzes the initiatives of the Republic of Uzbekistan within the framework of the United Nations and its role in global politics from 2016 to 2025. It thoroughly examines the main directions of cooperation with the United Nations, priority principles, promising projects, achievements in implementing the Sustainable Development Goals, and significant reforms in the field of human rights. Additionally, the article discusses the increasing role of the Republic of Uzbekistan in the international arena, its transformation into a significant participant in global politics, and the prospects for the continuation of this trend.